2020
DOI: 10.1002/for.2729
|View full text |Cite
|
Sign up to set email alerts
|

A performance analysis of prediction intervals for count time series

Abstract: One of the major motivations for the analysis and modeling of time series data is the forecasting of future outcomes. The use of interval forecasts instead of point forecasts allows us to incorporate the apparent forecast uncertainty. When forecasting count time series, one also has to account for the discreteness of the range, which is done by using coherent prediction intervals (PIs) relying on a count model. We provide a comprehensive performance analysis of coherent PIs for diverse types of count processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…While these numbers improve with increasing sample size T and with increasing α, they become worse with increasing μ (which is equal to the variance of the equidispersed Poisson distribution). These results regarding the effect of estimation uncertainty on the forecasts are in line with the studies by Homburg et al [7,8]. Now, the question is how to incorporate the parameter uncertainty into the coherent forecasting.…”
Section: Poisson Inar(1) Dgpsupporting
confidence: 89%
See 3 more Smart Citations
“…While these numbers improve with increasing sample size T and with increasing α, they become worse with increasing μ (which is equal to the variance of the equidispersed Poisson distribution). These results regarding the effect of estimation uncertainty on the forecasts are in line with the studies by Homburg et al [7,8]. Now, the question is how to incorporate the parameter uncertainty into the coherent forecasting.…”
Section: Poisson Inar(1) Dgpsupporting
confidence: 89%
“…The effect of estimation uncertainty on coherent forecasts was investigated for selected models by Freeland and McCabe [5], Jung and Tremayne [12], Silva et al [21], Bisaglia and Gerolimetto [3], and more comprehensively for a large variety of count processes by Homburg et al [7,8]. The latter authors concluded that the coherent central PFs are usually only slightly affected by estimation error, whereas the non-central and the interval forecasts may suffer a lot from estimated parameters.…”
Section: Example 11mentioning
confidence: 99%
See 2 more Smart Citations
“…Although approximate risk forecasting might appear attractive at a first glance, because of simplified computations and readily available software implementations (e. g., Chan and Nadarajah 2019), it is not clear whether the obtained risk forecasts are indeed competitive to the coherent risk forecasts or they lead to a serious misjudgment of the actual risk. The studies of Homburg et al (2019Homburg et al ( , 2020 about point and interval forecasting of count time series may serve as a warning that approximate approaches might end up in rather misleading results. Therefore, besides a detailed analysis of coherent risk forecasting for various count processes in the presence of estimation uncertainty, we also investigate the performance of approximate risk forecasting in comparison to the coherent forecasting approach.…”
Section: Introductionmentioning
confidence: 99%